INTegrating Ice core, MArine and TErrestrial records (COST Action ES0907). - Hoek, W.; Rasmussen, S.; Renssen, H.; Hajdas, I.; Brauer, A.; Brockley, S.; Svensson, A.; Moreno, A.; Roche, D.; Valdes, P.; Birks, H.; Solveig-Seidenkrantz, M.; et al. (EGU General Assembly, 2013)
The objective of INTIMATE is to reconstruct past abrupt and extreme climate changes over the period 60.000 to 8000 years ago, by facilitating INTegration of Ice core, MArine, and TErrestrial palaeoclimate records and using the combined data in climate models to better understand the mechanisms and impact of change, thereby reducing the uncertainty of future prediction. The project is organized in four working groups: WG-1 Dating and Chronological Modelling A reliable chronological framework is the basis of all studies of the past climate. WG1 is dedicated to developing and improving dating methods over the last 60,000 years and bringing scientists together to develop a coherent dating framework in which records can be compared at unprecedented detail. WG-2 Quantification of Past Climate The aim of WG-2 is to collect and quantify information of past climate from e.g. ice cores, tree rings, corals, stalagmites, and marine and lake sediments in order to draw a detailed picture of the highly variable climate evolution in the North Atlantic region. WG-3 Modelling Mechanisms of Past Change Our ability to forecast the rates and magnitudes of future change depends on numerical models. By using combined ice core, terrestrial, and marine data sets as targets, WG-3 will optimize methodologies to evaluate model simulations and make data-model comparisons. WG-4 Climate Impacts The aim of WG-4 is to gain insights into the impacts of past climatic changes on animal and human populations and the ecosystems of which they are part. WG-4 will quantify the magnitudes and rates of population, species, and ecosystem responses to climate events of different magnitudes in space and through time.